Design, manufacturing, numerical analysis and environmental effects of single-pass forced convection solar air collector - Alic, Erdem; Das, Mehmet; Akpinar, Ebru Kavak (Elsevier Sci Ltd, 2021)
Solar air collectors (SACs) are one of the best methods of utilizing renewable energy sources. The increasing need for quality and suitable energy was led to the require for further development of many known engineering applications. In this study, four different absorber plate SACs were designed using exergy-based methods (exergetic indicators) to assess the environmental effects of SAC. Their thermal performance and exergy efficiencies were determined. Also, absorber plate geometric configurations of SAC were examined. These SACs were single pass and forced convection collectors. One of the designed collectors (Das Model) was manufactured and tested at constant mass flow and different times under Elazig province climatic conditions in Turkey. The numerical analysis method was made with the computational fluid mechanics (CFD) program. For this purpose, 3D models of the SACs were drawn. The error values of the models obtained in CFD analysis were less than 1%. The differences between the thermal efficiency, friction factor and manufacturing methods of the solar collector were investigated. In addition, the behavior of some exergetic indicators on the performance of the SACs and the environmental effects of the collectors were investigated. Therefore, some of exergetic factors were taken into consideration including exergy effect, waste exergy ratio (WER), environmental impact factor (EIF), exergetic sustainability index (ESI) and improvement potential (IP). Finally, energy-based environmental impact analyzes were conducted for the life cycle assessment of SAC. A SAC model was determined to less environmental impact than others.
Keywords: Solar air collector; Cleaner design; CFD; Renewable energy; Environmental impact analysis